Toothbrush bristle configuration and brushing load: Effect on the development of simulated non-carious cervical lesions. (July 2019) - Turssi, Cecilia P.; Kelly, Adam B.; Hara, Anderson T.
Abstract: Objectives: This study investigated the effect of toothbrush bristle configuration and brushing load on the development of non-carious cervical lesions (NCCLs). Methods: Human premolars were mounted on acrylic blocks and had their root surfaces partially covered with acrylic resin to simulate gingiva, leaving a 2-mm length area apical to the cemento-enamel junction exposed for brushing. The teeth were brushed under 1- or 3 N load with one of the following toothbrushes (n = 16): a) ordinary/flat-trimmed (Oral-B Indicator); b) rippled (Oral-B Contour); c) cross-angled/multileveled/rubber bristles (Oral-B Pro-Health All-in-One); d) cross-angled/multileveled/flex head (Oral-B Pro-Flex); e) feathered (Oral-B Compact Clean). Brushing was performed using toothpaste slurry (Crest Cavity Protection) for 55, 000 double-strokes in back-and-forth motion, to simulate 10 years of brushing. Impressions were taken at baseline and after brushing and scanned by a 3D optical profilometer. The lesions formed were evaluated for volume loss, angle, and shape. Results: The ordinary/flat-trimmed toothbrush caused significantly higher volume loss (3.81 mm 3 ) in comparison to the other toothbrushes (2.56-2.92 mm 3 ). The toothbrush having rubber bristles was associated with NCCLs showing the smallest angle and, along with the rippled toothbrush (53.1%), provoked higher proportion of wedge-shaped lesions (43.8%), whereas teeth brushed with the feathered toothbrush exhibited the lowest prevalence of wedge-shaped lesions (3.1%). The 1- and 3 N load applied during brushing affected neither volume loss nor lesion angle. Conclusions: At the brushing loads tested, the development of NCCLs was dependent on toothbrush bristle configuration, with the ordinary/flat-trimmed version causing the highest abrasion and the feathered toothbrush the least proportion of wedge-shaped lesions. Clinical significance: Toothbrush bristle arrangement plays a role in NCCL development, with the ordinary/flat-trimmed version being more abrasive and the feathered toothbrush causing less wedge-shaped lesions.